Linking safety knowledge, attitude, and behaviour among manufacturing workers in Malaysia: a PLS predict approach - Syazwan Syah, Zulkifly; Yusmani, Mohd Yusoff; Nor Halim, Hasan; Mohd Rafee, Baharudin; Fernando, Yudi (Inderscience Publisher, 2025)
The manufacturing sector recorded the highest accident cases in Malaysia, and safety behaviour was found to have been the leading cause. The theory of reason action (TRA) proved that attitude could spark intention and lead to behaviour. However, the role of knowledge in influencing behaviour remains ambiguous, and this study applied a research model in which safety knowledge, safety attitude, and safety behaviour were investigated among Malaysia’s manufacturing workers. A questionnaire survey was distributed to 100 respondents who work in manufacturing firms. The data were analysed using partial least squares structural equation modelling. As a result, safety attitude and knowledge significantly affected safety behaviour, with safety attitude mediating. Furthermore, the PLS predict results determined a high predictive power of the research model. This finding extends previous research by highlighting the roles of safety knowledge and attitude in mediating the relationship between safety knowledge and safety behaviour. The KAB approach is a theoretical foundation for understanding the relationships between safety behaviours, safety knowledge, and safety attitudes. Moreover, the study is unique because it incorporates safety knowledge to predict safety attitudes and affect safety behaviours in the context of the theory of planned behaviour (TPB) and theory of reason action (TRA).